Thrombolysis for stroke in pregnancy at 39 weeks gestation with a subsequent normal delivery. (11th August 2015) - Ritchie, Joanne; Lokman, Mariam; Panikkar, Jane
Abstract : Stroke during pregnancy is fortunately a rare event, however, it can have severe consequences, with 9.5% of all maternal deaths being related to stroke. The most common presentation is an ischaemic stroke. There has been much debate as to the correct treatment for such cases' and whether thrombolysis can be used safely in pregnancy. Our case describes a 28-year-old woman with a previous normal vaginal delivery presenting in her third trimester with a sudden onset of dense left hemiparesis. She was successfully treated with alteplase, an intravenous recombinant tissue-type plasminogen activator, and made a full recovery after normal delivery of a healthy infant. This case report highlights one of the first documented successful outcomes from thrombolysis for this condition in the UK and may help inform future management of these women.